2020
DOI: 10.1017/s0950268820002058
|View full text |Cite
|
Sign up to set email alerts
|

Bias correction methods for test-negative designs in the presence of misclassification

Abstract: The test-negative design (TND) has become a standard approach for vaccine effectiveness (VE) studies. However, previous studies suggested that it may be more vulnerable than other designs to misclassification of disease outcome caused by imperfect diagnostic tests. This could be a particular limitation in VE studies where simple tests (e.g. rapid influenza diagnostic tests) are used for logistical convenience. To address this issue, we derived a mathematical representation of the TND with imperfect tests, then… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…2C,D). The uncorrected estimates systematically underestimated vaccine effectiveness aligning with analytical predictions [4].…”
Section: Imperfect But Known Sensitivity and Specificitysupporting
confidence: 70%
See 4 more Smart Citations
“…2C,D). The uncorrected estimates systematically underestimated vaccine effectiveness aligning with analytical predictions [4].…”
Section: Imperfect But Known Sensitivity and Specificitysupporting
confidence: 70%
“…2). Thus, while several preceding studies have shown that estimates can be made unbiased by adjusting for sensitivity and specificity [5,3,4], here we further showed that test performance affects vaccine effectiveness uncertainty even after bias adjustment, leading us to conclude that there is independent value in high-performance diagnostic testing, even if signals may be statistically debiased a posteriori.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations